Unhealthy competition among Radio Stations and the fight to keep-up with broadcast ethical standard: An assessment of Imo State Radio broadcast journalists - Anele, Miracle Chukwuemeka; Etumnu, Emeka Williams; Okalla, Fabian; Ogu, Clinton Chukwuma (Universitas Ahmad Dahlan, 2023)
This study assessed the influence of unhealthy competition among radio stations in Imo State and how it affects their adherence to broadcast ethical standards. This study was anchored on the Social Responsibility Theory. This study employed a mixed-methods research design that made use of a survey and an in-depth interview. The population of the study comprised 180 NUJ members in Imo State. The instruments for data collection were the questionnaire and an in-depth interview guide. Findings showed that station owners and their journalists understand the ethical codes of their profession. At an average mean of 2.8 radio stations in Owerri, they can uphold the ethical standard of their profession by creating a sustainable image before their listeners, sticking strictly to the NBC and NUJ ethical codes and the punishment of defaulting journalists in their station, taking personal decisions, and sticking by them to be the best change they want to see in the world even as they do their day-to-day work. It was concluded that the establishment of more radio stations in Imo State makes existing radio stations struggle in their fight to keep up with NBC ethical standards, even as they are confronted with competing radio stations here and there. The researchers recommend that station owners and their staff should be up in their game to be unique, irrespective of other radio stations coming to join them for the same or similar clients and profits. This will go a long way toward making their staff formidable to face the worst of situations.